Interactive Learning Media Loaded with Human Growth and Development Materials in Science Learning in Elementary Schools that is Decent and Practical: Media Pembelajaran Interaktif, IPA, Articulate Storyline 3 - Safti Putri, Nur; Hendrik, Maulina; Romadhon , Romadhon (Universitas Negeri Surabaya, 2024)
Interactive learning media is needed to improve the quality of science learning in elementary schools. The purpose of this study is to produce interactive science learning media for growth and development materials in grade 3 of elementary school. This research method is in the form of research and development (R&D) with the ADDIE development model. This article focuses on the